Financial distress: a study of companies that are classified as PN4 at Bursa Malaysia Berhad / Patricia Yolander James - James, Patricia Yolander (2006)
This project is attempted to study the relationship between leverage ratio and liquidity ratio with the companies’ performance of the companies classified as PN4. Net profit margin is uses to measure the companies’ profitability. The objective is to see the performance of the companies in PN4 categories before and after they are classified as PN4. This study has been conducted based on the ten out of twenty-one companies classified as PN4 as at 30 December 2005. The ten companies are selected randomly from the sample size. The study will cover the period of five years, that is two years before the companies classified as PN4, the year the companies enter PN4 and two years after the companies classified as PN4. The name and some descriptions of the sample are included under the population and sample size. In the report finding I will analyze the leverage ratio and liquidity ratio using the descriptive analysis and Pearson Correlation.